2017
DOI: 10.21325/jotags.2017.127
|View full text |Cite
|
Sign up to set email alerts
|

Veganların Restoranlarda Karşılaştıkları Sorunlar Üzerine Bir Araştırma (A Research on the Problems of Vegans Compare in Restaurants)

Abstract: Vegan Restoran Sorunlar İçerik analizi ÖzBu çalışmada farklı tüketici gruplarının farklı beklentileri ve tercihleri olduğu gerçeğinden yola çıkarak yiyecek-içecek sektörünü ilgilendiren ve bugüne kadar araştırmalarda çok fazla değinilmeyen bir konu olan veganların restoranlarda karşılaştığı sorunları gün yüzüne çıkarmak amaçlanmıştır. Araştırmada veriler açık uçlu soru formu ile sosyal medyadaki vegan gruplardaki kişilerden toplanmış olup nitel analiz tekniklerinden içerik analizi ve betimsel analiz ile verile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Among those multiple causes, the first case is methodological cooking skills, including hygiene and sanitation. Both Vegan/Vegetarian and Celiac travelers usually cautious about the cross-contamination with different angles (Comert, & Durlu Ozkaya, 2014;Sunnetcioglu et al 2017). To get rid of these problems, gluten, and gluten-free operations must be separated.…”
Section: Discussionmentioning
confidence: 99%
“…Among those multiple causes, the first case is methodological cooking skills, including hygiene and sanitation. Both Vegan/Vegetarian and Celiac travelers usually cautious about the cross-contamination with different angles (Comert, & Durlu Ozkaya, 2014;Sunnetcioglu et al 2017). To get rid of these problems, gluten, and gluten-free operations must be separated.…”
Section: Discussionmentioning
confidence: 99%
“…When we look at the studies directly related to veganism in the field of tourism, it is revealed that there is a limited number of studies. Vegan related tourism researches are about experiences (Kansanen, 2013Oh vd., 2021; motivations (Li, Liu, Cai, Scott, 2020); expectations (Tural, 2018); problems faced at restaurants (Sünnetçioğlu et al, 2017); vegan-vegetarian hotel concept Dilek (2018); hotel coices (Dilek ve Fennell, 2018); Definition of vegan/vegetarian tourist Vatan ve Türkbaş (2018); Vegan/vegetarian festivals (Aktaş, Şen ve Çil (2019); Sustainable tourism relation (Dilek ve Dilek, 2020); Current position of vegan tourism (Çetin, 2021).…”
Section: Veganism and Vegan Touristsmentioning
confidence: 99%
“…TARTIŞMA, SONUÇ ve ÖNERİLERMercan, Türkmen, Yıldırım ve Sünnetçioğlu (2017) araştırmalarında vegan bireylerin restoranlarda karşı karşıya geldikleri problemleri incelemiş ve çalışma sonucunda, veganların menülerinde bulunan ürünlerde hayvansal gıdalar kullanılmasından KAYNAKÇA Abhijat, S. R. and Routray, S. S. (2022). Where Does the Privilege in Veganism Come From?…”
unclassified